Toward a framework that connects individual TPACK and collective TPACK: A systematic review of TPACK studies investigating teacher collaborative discourse in the learning by design process - Yeh, Yi-Fen; Chan, Kennedy Kam Ho; Hsu, Ying-Shao (Computers and education, 2021)
“Learning by design” is a widely used approach for developing teachers' technological pedagogical content knowledge (TPACK) in the context of designing technology-enhanced instruction. This approach offers teachers the opportunity to learn from colleagues with different areas of expertise. Despite the critical importance of teachers' collaborative discourse in mediating teacher learning in the design process, there has not yet been a TPACK review to analyze how researchers investigate this discourse. After a systematic literature search, we identified eleven TPACK studies from seven geographical regions that investigated teachers' collaborative discourse, and then examined how the researchers had structured and analyzed this discourse and integrated their findings. Our analysis identified four strategies used by the researchers to structure and promote teachers' collaborative discourse. We found that most studies relied on the “coding and counting” data analysis method to reveal the distribution of TPACK (sub)sets expressed in the collaborative discourse but not the dynamics of the knowledge construction process or the progression of the discourse. Although the studies generally provided initial evidence for the efficacy of the design process, this evidence was rarely based on changes in teachers' TPACK as enacted during classroom instruction or on the quality of the design outcomes. We thus propose a new conceptual framework that emphasizes the reciprocal knowledge exchange process between the TPACK of individual teachers and the knowledge shared by teachers through collaboration. This framework refocuses the attention of researchers on investigating and connecting teachers’ individual and collective TPACK and their development during the learning by design process. •Eleven TPACK studies were identified that investigated teachers' collaborative discourse.•How TPACK researchers investigated teacher collaborative discourse was analyzed.•Research designs and related findings in the field were synthesized and appraised.•Strategies to promote productive teacher collaborative discourse were identified.•A TPACK framework connecting personal, collective and enacted TPACK was proposed.